Florestamento - desenraizamento : a transformação da paisagem nos pampas e a identidade do gaúcho - Schwanz, Angélica Kohls (2010)
The goal of this paper is to discuss the implications of the identity of the gaucho, from hunges in the landscape of the Pampa rio-grandense, located in the "southern haif" of Rio Grande do Sul. The changes were accelerated from the year 2004, with the announcement of the cxpansion of plantation forests for the extraction of cellulose. I assume that the identity of the gaucho and the relationship this has with the environment are so rooted in their making, that radical change as it has been processed in that space, can affect your way to fall in the world. The landscape is understood from a cultural approach therefore consists in the relationship with the man. To apprehend this relationship were used, from my insertion site, the oral reports of local residents. Understanding how these transformations occur through the eyes of residents to assess the extent of the impacts of monocultures in the formation of memories and identities.